"Please mind the gap": A secondary analysis of discomfort and comfort in intensive care. Issue 13 (17th April 2020) - Berntzen, Helene; Bjørk, Ida Torunn; Storsveen, Ann‐Marie; Wøien, Hilde
Abstract: Aims and objectives: To explore in depth discomfort in intensive care as experienced by patients and attended to by critical care nurses. Background: Discomfort in illness is complex and persistent, and its alleviation is a challenge for nurses working in intensive care units (ICU). In previous studies, we showed that ICU patients described little actual pain but suffer from much discomfort. Critical care nurses had a systematic approach to the treatment of pain, but were more haphazard in dealing with other types of discomfort. Design: Secondary qualitative analysis of data from two previous exploratory studies. Methods: Content analysis was used on existing data from 28 interviews with ICU patients, and 16 field notes and interviews with critical care nurses. Kolcaba's Comfort Theory was applied for further analysis. The COREQ checklist was used. Results: Three themes, "Being deprived of a functioning body", "Being deprived of a functioning mind" and "Being deprived of integrity" characterised the discomfort experienced by ICU patients. The nurses appeared to attend to all areas of discomfort expressed by patients. In need of, and providing acknowledgment and alleviation became a common overarching theme. We identified a comfort gap caused by the discrepancy between the patients' needs and the nurses' achievements in fulfilling these needs. Conclusions: A gap exists between ICU patients' comfort needs and nurses' achievements in fulfilling these, indicating that discomfort currently is an inevitable part of the critical illness trajectory. Increased knowledge about how the brain is affected in ICU patients and more systematic approaches to assessing comfort needs and enhancing comfort may support nurses in fulfilling patient needs and possibly diminish the existing comfort gap. Relevance for clinical practice: An increased understanding of the complex experience of discomfort in ICU patients may bring about more systematic approaches to enhance comfort and direct for education and further research.